Penerapan Basis Data pada Sistem Manajemen Laundry - Zebua, Silvia; Bancin, Trisnawati; Pandia, Mahdianta (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The advancement of technology has opened opportunities for entrepreneurs to manage data more efficiently and reduce the risk of data loss or misplacement. In the past, laundry services were only available in hotels as a facility for guests. However, over time, laundry services can now be found in various locations and accessed without the need to visit a hotel. I am planning to develop a Laundry Information System, which I will name. This system will not only function to manage data securely and efficiently but also to expedite the process of searching for customer data. Additionally, will allow customers to monitor the status of their laundry tasks. Customers no longer need to visit the laundry facility to wash their clothes. By simply placing an order, a courier will pick up the clothes for laundering and deliver them back once completed.